Heme oxygenase-1 and iron in liver inflammation: a complex alliance - Immenschuh, Stephan; Baumgart-Vogt, Eveline; Mueller, Sebastian (Current drug targets, 2010)
Heme oxygenase (HO)-1 is the inducible isoform of the first and rate-limiting enzyme of heme degradation. HO-1 has potent antioxidant and also anti-inflammatory functions, the underlying mechanisms of which are not well understood. Together with antioxidant carbon monoxide and biliverdin, HO produces reactive iron, which unambiguously connects this enzyme with the iron metabolism and its potential toxicity. A link between HO-1 and iron homeostasis has been demonstrated in HO-1 knockout mice, which develop major hemosiderosis in solid organs such as liver and kidney. Moreover, genetic HO-1 deficiency causes a chronic inflammatory condition in these animals. As the liver plays a crucial role for the bodys iron homeostasis (e.g. via secretion of the iron regulatory hormone hepcidin) and also for systemic inflammation, hepatic HO-1 may be important for the regulation of both systems. In particular, cell-specific functions of HO-1 in liver tissue macrophages (Kupffer cells) might be of major significance, because these cells play a key role in iron recycling during erythrophagocytosis and also in the control of hepatic and systemic inflammatory responses. This review discusses the current knowledge on interactions of HO-1 with iron metabolism in the context of systemic as well as hepatic inflammatory disorders. Recent advances in the understanding of the functional role of HO-1 in inflammatory liver diseases, namely viral hepatitis, alcoholic liver disease and non-alcoholic steatohepatitis are summarized. Finally, it is highlighted, how targeted modulation of HO-1 may provide specific protection in these inflammatory disorders.